If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 10 + -4p + 35 = 2 + -1p Reorder the terms: 10 + 35 + -4p = 2 + -1p Combine like terms: 10 + 35 = 45 45 + -4p = 2 + -1p Solving 45 + -4p = 2 + -1p Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add 'p' to each side of the equation. 45 + -4p + p = 2 + -1p + p Combine like terms: -4p + p = -3p 45 + -3p = 2 + -1p + p Combine like terms: -1p + p = 0 45 + -3p = 2 + 0 45 + -3p = 2 Add '-45' to each side of the equation. 45 + -45 + -3p = 2 + -45 Combine like terms: 45 + -45 = 0 0 + -3p = 2 + -45 -3p = 2 + -45 Combine like terms: 2 + -45 = -43 -3p = -43 Divide each side by '-3'. p = 14.33333333 Simplifying p = 14.33333333
| 15p+17q+p-7q-4p= | | -0.04x-x-0.2x=6.2 | | 8-16w=-8(1+2w) | | 8x+2=x-3 | | 4x-9+3x-5+x=7x+2 | | 0.6666667x+6=0.5x+0.25x | | g(h)=-x^2+x-6 | | x^2+y^2-4x-6y+8=0 | | a-3b-2a= | | 25x-30=10x | | x^2+y^2-4x+6y+8=0 | | -10-(-2)= | | 143-2x=43x+18 | | 2.3x-5.4=-10 | | 7(x-3)-4x=-16 | | (x+1)=0 | | (2x+9)=x-3 | | 6x+18y=24 | | 18x+6y=24 | | 8(3n-2)= | | 14-10x=48-24x | | 6x+16-x=7x+4 | | 3.2= | | 6(-2x-1)=-11(x+1) | | H+6=-22 | | -96-7x=9x+13 | | 3(y-4)=y-6 | | Ay+6=14 | | 6x+3.50=33.20 | | 9-3r=13 | | 6x+1=-92-7x | | 3(2x+1)-5=4(x-3) |